Appearance anxiety and loneliness: the mediating role of rejection sensitivity in patients with alopecia areata in Lahore Pakistan - Rehman, Sadaf; Jameel, Rabia; admin (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate the association involving appearance anxiety, rejection sensitivity and loneliness in patients with alopecia areata. Method: The correlational study was conducted from February to September 2020 at public-sector and private-sector hospitals in Lahore, Pakistan, and comprised alopecia areata patients of either gender aged 20-40 years. Data was collected using the Appearance Anxiety Inventory, the Appearance-based Rejection Sensitivity Questionnaire and the University of California-Los Angeles Loneliness Scale. Data was analysed using SPSS 23. Results: Of the 240 patients, 120(50%) each were males and females. The overall mean age was 28.39±3.87 years. Appearance anxiety and rejection sensitivity were positive predictors of loneliness (p<0.000), while rejection sensitivity was positively significantly mediated between appearance anxiety and loneliness (p<0.000). Conclusion: The association involving appearance anxiety, rejection sensitivity and loneliness was found to be significant. Key Words: Alopecia areata, Appearance anxiety, Rejection sensitivity, Loneliness.